Revisiting the progressive consumption tax: A business cycle perspective - Wolfgang Strehl (Freie Universität Berlin, School of Business & Economics, 2019)
This paper revisits the personal expenditure tax (PET), the most prominent version of a progressive consumption tax. The PET has a long intellectual tradition in economics, and the merits and demerits of this alternative to the personal income tax have been discussed at length. What has been missing in the literature so far, however, is a systematic account of its effect on the business cycle. This paper therefore seeks to add to the theoretical literature on the PET and the wider literature on automatic fiscal stabilizers by analyzing the PET's macroeconomic properties in a modern business cycle model. To this effect, the paper introduces a highly stylized PET into a standard New Keynesian DSGE model, derives a log-linear version of the model, and draws a comparison with the existing income tax. The model simulations show that the two tax systems lead to quite different macroeconomic dynamics. Furthermore, it is found that the PET yields welfare gains, relative to the income tax, for all the demand shocks considered. The PET yields welfare losses, however, under a supply shock.
urn:nbn:de:kobv:188-refubium-25390-5
Keywords: E2; E3; E32; E62; E52; 330; Progressive Taxation; Consumption Taxation; Business Cycles; DSGEModel; Welfare Analysis